Race Issues in Selected Contemporary American Novels - Rosenbreierová, Andrea (Univerzita Pardubice, 2016)
This bachelor thesis deals with racist issue in contemporary American novels, The Help, The Secret Life of Bees and The Dry Grass of August. It focuses on the discrimination against Afro-Americans, the segregation of black people and white people and the limitation of the rights of Afro-Americans. The thesis depicts the relations of black maids, the white children in the maids' charge and their parents. In addition to displaying various attitudes of white people towards racism, the work discloses examples of open and hidden racism as well.
Rasové otázky v současných amerických románech
Keywords: Afro-Americans; racism; segregation; Help; Secret life of Bees; Dry grass of August; Afroameričani; rasismus; segregace